The Influence of Education on Pregnancy Danger Signs on the Knowledge of Pregnant Women in the Coastal and Island Areas - Windatania Mayasari; Siti Rochmaedah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pregnancy is a normal and natural process in a woman, during which physical, psychological, and social changes occur. Complications during pregnancy are one of the factors contributing to the increase in maternal mortality rates. Maternal knowledge plays a crucial role in efforts to reduce maternal mortality; a lack of knowledge in recognizing the danger signs of pregnancy can lead to insufficient and delayed anticipation during pregnancy. The objective is to analyze the effect of education on pregnancy danger signs on the knowledge of primigravida pregnant women in the coastal and island areas of Talaga Kambelo, Huamual Subdistrict, West Seram Regency. This study employs a quantitative research method with a quasi-experimental design. The research design used is the One Group Pretest-Posttest Design, where a single group is given the same intervention, and tests are conducted before and after the intervention. Providing education about the danger signs of pregnancy to primigravida mothers in coastal and island areas of Talaga Kambelo has a significant impact, as there is an improvement observed before and after conducting health education.